Cultural values and management approach of Suluk leaders in Sabah - Aishah Tamby Omar; Romzi Ationg; Syamsul Azizul Marinsah (Penerbit Akademia Baru, 2019)
The aim of this paper is to investigate the relationship between cultural values and management approach among leaders. Data were collected from 100 leaders of Suluk ethnic from various organizations such as public, private and non-government organization. Partial Least Squares Structural Equation Modelling (PLS-SEM) were used to test the hypotheses. The findings show that there is a positive relationship between cultural values and management approach. Specifically, the relationship was found to be stronger for leaders who have a low power distance culture and entrepreneurial management practice. The study provides an important implication in term of cultural values on leaders practice such as planning, organizing, leading and controlling. To embedded on entrepreneurial practice, leader should lower their power distance by equally used the power such as encouraging subordinates to be involved in organization decisions. The study also contributes to the research on divergence theory by understanding that management practices are culture-bound.